Artificial Intelligence in the economic sector: prevention and responsibility - Antunes, Maria João (2021)
This book was developed in the scope of the Exploratory Project “Artificial Intelligence and Corporate Crime”, integrated in the Research Area “Risk-Transparency-Litigation” and as part of the project “Societal Challenges, Uncertainty and Law: Plurality | Vulnerability | Undecidability” of the Uni- versity of Coimbra Institute for Legal Research (UIDB/04643/2020), which is financed by national funds from FCT.